2014
DOI: 10.1021/am502246j
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited ZnO—Nanowire/Cu2O Photovoltaic Device with Highly Resistive ZnO Intermediate Layer

Abstract: Cl-doped ZnO-nanowire (Cl:ZnO-nws)/Cu2O photovoltaic devices were prepared by electrodeposition in aqueous solutions, and the effects of the insertion of the highly resistive ZnO (i-ZnO) layer has been demonstrated by an improvement of the photovoltaic performance. The Cl:ZnO-nws and i-ZnO layer were prepared by electrodeposition in a zinc chloride aqueous solution with saturated molecular oxygen and simple zinc nitrate aqueous solution, respectively. The i-ZnO layer was directly deposited on the Cl:ZnO-nws an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Based on the findings, all the samples before and after deposition of p-Cu 2 O thin film exhibited triangular with combination of pyramidal shape. This results was believed corresponding to [111]-plane of Cu 2 O in structural properties and consistent with previous reported study [10]. It was proved that both acidic (pH 6.3) and alkaline (pH 12.5) electrolytes facilitate contribution a stable condition for the growth of a Cu 2 O thin film [4].…”
Section: Morphological Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the findings, all the samples before and after deposition of p-Cu 2 O thin film exhibited triangular with combination of pyramidal shape. This results was believed corresponding to [111]-plane of Cu 2 O in structural properties and consistent with previous reported study [10]. It was proved that both acidic (pH 6.3) and alkaline (pH 12.5) electrolytes facilitate contribution a stable condition for the growth of a Cu 2 O thin film [4].…”
Section: Morphological Characterizationsupporting
confidence: 92%
“…It was observed that the small grains agglomerated to form larger and denser grains thereby the surface was covered well with more number of pyramid shaped grains after deposition of p-Cu 2 O thin film as shown in Fig. 3b and c. Thus, more crystallites agglomerate to forms grains and the surface mobility enhanced indirectly [5,10]. These results were good agreeement with the highest intensity of p-Cu 2 O thin film for pH 12.5 at 2 h. The FE-SEM images for n-Cu 2 O before and after deposition of p-Cu 2 O at 1 h and 2 h are shown below.…”
Section: Morphological Characterizationmentioning
confidence: 87%
“…The preparation of ZnO scaffold with a high conductivity must favor the electron transfer in the device and then the charge collection. According to Shinagawa et al, [ 32,36 ] the resistivity of the i-ZnO layer deposited in nitrate medium is several orders of magnitude higher than that prepared in chloride medium. The carrier concentration in as-grown ZnO NWs prepared in KCl with molecular oxygen precursor and low ZnCl 2 concentration was estimated at 6.2 × 10 19 cm −3 by Mora-Sero et al [ 33 ] and ≈10 20 by Konenkamp et al [ 34 ] The high carrier concentration is classically assigned to chlorine doping since chlorine content (defi ned as Cl/(Cl + Zn) at%) is found at about 1% in the NWs/NRs [ 32 ] and about 3% in the Z50 fi lms [ 30 ] and acts as an extrinsic donor dopant.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical properties of ZnO layers prepared from molecular oxygen in a 5 mM zinc chloride solution have been recently characterized by Izaki et al [ 32 ] By Hall effect measurements, they found a resistivity of 4.4 × 10 −2 Ω.cm with a carrier concentration of 2.5 × 10 19 and a mobility of 9.6 cm 2 V −1 s −1 . The initial fi lms were grown in KCl medium with molecular oxygen precursor in order to yield n-type doped ZnO with a rather high carrier concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The electrodeposition process has several advantages over other techniques including gas-phase deposition processes, but the conversion efficiency was limited at low level of 3.97% 2) . The short-circuit current density (Jsc) is a parameter affecting to the efficiency, and the maximum values of 7.4 and 7.1 mAcm -2 have been reported for the substrate- 2) and super-straight type PV devices of the electrodeposited Cu2O layer with a random orientation 3) . The <111>-oriented Cu2O layer has been prepared on Au (111) /Si (100) wafer substrate by elctrodeposition 4) and showed an increased mobility 5) , which closely related to the diffusion length of carriers and Jsc value.…”
Section: Introductionmentioning
confidence: 99%